2019
DOI: 10.1016/j.biopsycho.2019.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation bias and misconceptions: Pupillometric evidence for a confirmation bias in misconceptions feedback

Abstract: Word count: 5136 PUPILLARY RESPONSE TO FEEDBACK ABOUT MISCONCEPTIONS ! 2 Abstract It has long been supposed that the confirmation bias plays a role in the prevalence and maintenance of misconceptions. However, this has been supported more by argument than by empirical evidence. In the present paper, we show how different types of belief-feedback evoke physiological responses consistent with the presence of a confirmation bias. Participants were presented with misconceptions and indicated whether they believed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Some studies have reported a strong impact of worldview, reporting that worldview-threatening corrections (i.e., corrections of worldview-consistent misinformation through provision of worldview-inconsistent correct information) can be ineffective or even backfire (Ecker & Ang, 2019; Nyhan & Reifler, 2010). This effect has been interpreted as a cognitive bias in line with motivated reasoning accounts (Edwards & Smith, 1996; Sleegers et al, 2019; also see Kunda, 1990). However, it has been difficult to replicate these findings (T.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Some studies have reported a strong impact of worldview, reporting that worldview-threatening corrections (i.e., corrections of worldview-consistent misinformation through provision of worldview-inconsistent correct information) can be ineffective or even backfire (Ecker & Ang, 2019; Nyhan & Reifler, 2010). This effect has been interpreted as a cognitive bias in line with motivated reasoning accounts (Edwards & Smith, 1996; Sleegers et al, 2019; also see Kunda, 1990). However, it has been difficult to replicate these findings (T.…”
mentioning
confidence: 58%
“…Some studies have reported a strong impact of worldview, reporting that worldview-threatening corrections (i.e., corrections of worldview-consistent misinformation through provision of worldview-inconsistent correct information) can be ineffective or even backfire (Ecker & Ang, 2019;Nyhan & Reifler, 2010). This effect has been interpreted as a cognitive bias in line with motivated reasoning accounts (Edwards & Smith, 1996;Sleegers, Proulx, & van Beest, 2019; also see Kunda, 1990). However, it has been difficult to replicate these findings (Wood & Porter, 2019), and other studies have found that corrections can be equally effective irrespective of the source of the misinformation or its worldview congruence (Ecker, Sze, & Andreotta, 2021;Swire-Thompson, Ecker, Lewandowsky, & Berinsky, 2020;Weeks, 2015).…”
Section: Combining Refutations and Social Norms Increases Belief Changementioning
confidence: 99%
“…Under a so-called confirmation bias people search for, interpret, or recall evidence in ways that are biased toward confirming their existing beliefs; that is, people "test" their beliefs in a cherry-picking fashion by soliciting, recalling, and assimilating mainly confirmatory information and by focusing on one possible interpretation of the evidence while ignoring alternatives (Jelalian & Miller, 1984;Nickerson, 1998). Although a confirmation bias occasionally may be defensible (e.g., in the context of a belief about impending danger, Dudley & Over, 2003; or when there are hardly any alternative beliefs, Perfors & Navarro, 2009), in most situations this strategy of selective attention appears to be a defensively-driven impediment to the on-going critical evaluation of existing beliefs (Klayman, 1995;Sleegers et al, 2019). Confirmation bias has been described as ubiquitous (Nickerson, 1998) and "the most insidious of all cognitive errors" (Hollier, 2016, p. 1), and it is usually construed as an unconscious heuristic that is inaccessible to introspection (Nickerson, 1998), although Anglin (2016) has shown that some people are aware of this bias in themselves.…”
Section: Confirmation Biasmentioning
confidence: 99%
“…For example, Hameleers and van der Meer’s (2020) experimental study showed that individuals were more likely to avoid fact-checkers—a potential solution to correct misinformation—that were incongruent with their prior attitude, providing evidence that the persistence of misinformation might be partly a result of confirmation bias. Investigating pupillometry as a physiological measure indexing psychological processes, Sleegers et al (2019) found that people tended to interpret ambiguous feedback on their incorrect beliefs in favor of the beliefs they held, demonstrating a confirmation bias process underlying the persistence of incorrect beliefs. Data-driven models with massive social media data also suggest that confirmation bias is a key determinant for misinformation spreading and attitude polarization (e.g., Del Vicario et al, 2016).…”
mentioning
confidence: 99%